Speed-Breeding System in Soybean: Integrating Off-Site Generation Advancement, Fresh Seeding, and Marker-Assisted Selection - Fang, Yudong; Wang, Liwei; Sapey, Enoch; Fu, Shuai; Wu, Tingting; Zeng, Haiyan; Sun, Xuegang; Qian, Shuqing; Khan, Mohammad Abdul Awal; Yuan, Shan; Wu, Cunxiang; Hou, Wensheng; et al. (Frontiers in Plant Science, 2021)
Speed breeding by artificial control of photothermal conditions facilitates generation advancement but was limited in scale and cost. In this study, we demonstrated a cost-saving off-site summer nursery pattern, taking full advantage of shorter daylength and higher temperature with lower latitude compared to the origin of the soybean cultivars used in the study. This substantially reduced the generation cycles under totally natural conditions. Using this approach, two generations of soybean cultivars of Northeastern were successfully completed during summer in Beijing and winter in Hainan, compared to one generation each in Northeast China and Hainan. Fresh seeding method was also used to further shorten generation duration by 7-10 days, thereby allowing at least four generations per year. Using DNA markers to defined haplotypes of maturity genes E1-E4, we propose a model to predict optimum adaptation region of the advanced generation lines. Taken together, we present a speed breeding methodology combining off-site nursery, fresh seeding method and marker-assisted selection (MAS), aimed at accelerating soybean improvement.